Re(presenting) habit - Rossi, Stefani M., author; Yust, Dave, advisor; Sullivan, Patrice, advisor; Flippen, Paul, committee member; Lehene, Marius, committee member; Aoki, Eric, committee member; DiCesare, Catherine R., committee member (Colorado State University. Libraries, 2010)
In my work, I cultivate intimate encounters that invite people to contemplate the larger narratives in which we participate. I (re)present objects in order to create microcosms of these narratives. Over the last three years, my interest in stories revealed by artifacts of daily living, particularly those used in significant routines, led to my investigation of the lingering evidence of habitual consumption: receipts, wrappers, and disposable containers. When recontextualized, these ephemera remain potently descriptive of the activities for which they were originally purposed. The things we live among, what we strive to possess, the detritus we try to eliminate—these all shape our notions regarding beauty, position, status, and belonging. Through staged scenarios that incorporate carefully rendered illusions of trash, sometimes incorporating the material presence of these leftovers themselves, In Memoriam construes habitual consumption to be an act of petition, a process of recollection, and an expression of devotion.
Department Head: Gary Wayne Voss.